Laponite®: a key nanoplatform for biomedical applications? - Tomás, Helena (2019)
Laponite® is a synthetic smectite clay that already has many important technological applications, which go beyond the conventional uses of clays in pharmaceutics and cosmetics. In biomedical applications, particularly in nanomedicine, this material holds great potential. Laponite® is a 2-dimensional (2D) nanomaterial composed of disk-shaped nanoscale crystals that have a high aspect ratio. These disks can strongly interact with many types of chemical entities (from small molecules or ions, to natural or synthetic polymers, to different inorganic nanoparticles) and are also easily functionalized and readily degraded in the physiological environment giving rise to non-toxic and even bioactive products. This review will highlight the potential of Laponite® as a nanomaterial in the fields of drug delivery, bioimaging, tissue engineering and regenerative medicine. New concepts, as well as novel innovative materials that stand out from the usual ones due to the unique properties of Laponite®, will also be presented and discussed.